(untitled) (Research, Society and Development, 2022)
This study aimed to compare the self-esteem of adolescents who practice and do not practice physical activity. The research was carried out in a descriptive way with a cross-sectional design. The sample used for data collection consisted of 50 adolescents aged between 13 and 17 years, of both sexes, students from private and public schools in the city of Ubá-MG. Two instruments were used, the short version of the International Physical Activity Questionnaire and the Rosenberg Self-Esteem Scale. It was possible to observe through the results that most adolescents are physically active, representing 76% of the sample, and that they have a better self-esteem in relation to those who are insufficiently active (10.58+ 6.35 and 15.00+ 5.49, respectively). The male subjects also showed higher self-esteem compared to females, with an average of 14.00+ 5.78 and 7.44+ 5.27, respectively. These results show that physical activity interferes with adolescents’ self-esteem and that practitioners have better self-esteem compared to non-practitioners.